PENGARUH DEWAN KOMISARIS INDEPENDEN TERHADAP NILAI PERUSAHAAN SUB SEKTOR PERKEBUNAN YANG TERDAFTAR DI BEI - Iroh Rahmawati (Progress: Jurnal Pendidikan, Akuntansi dan Keuangan, 2021)
Good corporate governance can signal the existence of harmonious interests between all stakeholders, thereby reducing conflict. In addition, company management can also achieve company goals, namely increasing company value. Firm value is the shareholder's perception of the company's success in managing its resources, which is reflected in the company's share price. This study aims to determine the effect of the independent board of commissioners on the company value of the plantatio sub-sector listed on the IDX. The population in this study were plantation sector companies listed on the Indonesia Stock Exchange in 2017-2018. Sampling was done by using purposive sampling, the sample used which met the standards is as many as 8 companies. The analysis used is a simple linear regression analysis by performing the classic assumption test, namely, normality test, multicollinearity, and autocorrelation. The results showed that the independent board of commissioners had an effect on firm value.